Chemistry Anxiety Among Bachelor-Level Students in Science Education - Ghimire, Paras Mani (Ganeshman Darpan, 2023)
This research aims to investigate the reasons for anxiety among Bachelor’s level Chemistry students. This study adopted a phenomenological research approach to elicit in-depth responses from teachers and students about their lived experiences and perceptions that cause anxiety in science classes due to the chemicals in the lab. The data was collected through in-depth interviews with students who suffer from anxiety in Chemistry classes. This study tried to uncover some of the roots of scientific fear. The interviews resulted in clear descriptions of the pupils’ anxiousness. Fear appears to be linked to language issues, instructional approaches, and perception of chemistry views the student’s main source of anxiety is the language problem. Understanding the causes of science anxiety may also help educators construct more effective classes. They can think about the reasons for worry in these students and create some experiences for them to motivate them to complete the course. If teachers are aware of the issues that arise from students’ chemistry anxiety, they can assist students in reducing their worry. furthermore, they can focus more effectively on course activities and materials. Using visual resources, asking questions, and creating activities that require active student participation, the instructor can help students overcome their passive approach to the subject during a lecture.